As relações institucionais na aprovação anual da proposta orçamentária em nível federal: um estudo comparado entre o Brasil e o México - Oliveira, Carla Patricia Mania de (Universidade Federal de São Carlos, 2018)
The present work is a comparative study between Brazil and Mexico, at a Federal Level, approaching the institutional relations in the coalition government during the annual budget cycle stage aiming at evaluating of proposals for public resource allocation. The scope leads this studies to an analysis of Executive Branch and Legislative Power interactions in the decision -making process of budget arena and mutual influence in the definition of annual public spending by modifying the initial proposal, amending and approving it. This stage involves a complex political negotiation where the participants have distinct incentives and they aim determine budgetary initiatives which will deserve the resources allocation to the detriment of other possibilities. The aim is to understand institutional relationship, limits of the activities, incentives of participants and the boundaries of inter-party and inter-institutional cooperation which leads to approval of budget proposal. In this way, this research makes a review of the institutional condition and the structure of budgetary institutions of each country, a systematic analysis of the organization and transparence , dynamics of the decisions, competences and prerogatives of participants, the extent of decision makers, external sources of pressure, structure of public spending, the constraints on resource allocation an re-allocation and the dimensions actually available for change. The research is carried out through a bibliographic and documentary procedure, with a qualitative approach, exploratory descriptive objective from a comparative perspective of Brazilian and Mexican institutional scenarios from 1988 and 1997, respectively.
Keywords: Presidencialismo de coalizão; Orçamento público; Relações institucionais; Brasil; México; Coalition presidentialism; Public budget; Institutional relations; Brazil; Mexico; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::POLITICA E PLANEJAMENTO GOVERNAMENTAIS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA